Derivation of Sa-MoDEI score from DEI. Tak for prognostication in Buerger's Disease - Preliminary data of a prospective observational cohort - Gregory Pathrose; Albert A Kota; Prabhu Premkumar; Prasanna Samuel; Shivraj Padiyar; Deepak Selvaraj; Prasanta Padhan; Debashish Danda (Indian Journal of Rheumatology)
Background: Buerger's disease or thromboangitis obliterans (TAO) is a segmental occlusive inflammatory condition of vessels. Assessment of disease activity in TAO is challenging. There is no dedicated prognostication score available till date for Buerger's disease. Hence, our aim was to prognosticate outcomes in patients with diagnosed Buerger's disease using Sa-MoDEI score, a novel disease extent index (DEI) derived and modified from DEI. Tak score used in Takayasu's arteritis. Patients and Methods: In this prospective observational study, patients with TAO presenting to the Department of Vascular Surgery from June 2007 to April 2009 were studied. Shinoya's criteria were used to diagnose patients with Buerger's disease. Patients were scored on the basis of vascular, laboratory, and other clinical presentations as detailed in the Sa-MoDEI pro forma. They were followed up for 12 months after baseline scoring. Amputation was considered a bad outcome. The receiver operating characteristic curve was used to delineate a specific cut-off Sa-MODEI score to define bad outcomes. Factors associated with bad outcomes were analyzed using Cox proportional hazards model. Results: There were 84 patients with Buerger's disease. All were male with a significant history of tobacco use (smoking cigarettes or “beedis” [leaf cigarettes used in south Asian nations especially in countryside], chewing tobacco, and inhaling snuff). The mean age was 39 years (standard deviation [S. D] ± 6.8). Duration of smoking was 15.35 years (S.D ± 6.2); 65 patients were in good outcome and 19 patients in bad outcome group. The optimal Sa-MoDEI score cut-off for the bad outcome was 8 which corresponded with Youden's Index. Independent factors associated with bad outcome on multivariate analysis were age of onset below 39 years (Hazard Ratio [HR] = 6.00, 95% confidence interval [CI] (1.35–26.67), P = 0.019) and Sa-MoDEI score above 8 (HR = 9.77, 95% CI (2.60–36.71), P = 0.001). Conclusions: Sa-MoDEI score can be used as a tool to predict limb salvage in Buerger's disease.